Protein adsorption on poly(N-isopropylacrylamide) brushes dependence on grafting density and chain collapse - Xue, Changying (Langmuir : the ACS journal of surfaces and colloids, 2011)
The protein resistance of poly(N-isopropylacrylamide) brushes grafted from silicon wafers was investigated as a function of the chain molecular weight, grafting density, and temperature. Above the lower critical solution temperature (LCST) of 32 °C, the collapse of the water-swollen chains, determined by ellipsometry, depends on the grafting density and molecular weight. Ellipsometry, radio assay, and fluorescence imaging demonstrated that, below the lower critical solution temperature, the brushes repel protein as effectively as oligoethylene oxide-terminated monolayers. Above 32 °C, very low levels of protein adsorb on densely grafted brushes, and the amounts of adsorbed protein increase with decreasing brush-grafting-densities. Brushes that do not exhibit a collapse transition also bind protein, even though the chains remain extended above the LCST. These findings suggest possible mechanisms underlying protein interactions with end-grafted poly(N-isopropyl acrylamide) brushes